Natural polymers. Volume 2, - John, Maya J.; Thomas, Sabu (Royal Society of Chemistry, 2012)
In the search for sustainable materials, natural polymers present an attractive alternative for many applications compared to their synthetic counterparts derived from petrochemicals. The two volume set, Natural Polymers, covers the synthesis, characterisation and applications of key natural polymeric systems including their morphology, structure, dynamics and properties. Volume one focuses on natural polymer composites, including both natural and protein fibres, and volume two on natural polymer nanocomposites. The first volume examines the characterization, life cycle assessment and new sources of natural fibres and their potential as a replacement for synthetic fibres in industrial applications. It then explores the important advancements in the field of wool, silk, spidersilk and mussel byssus fibres. The second volume looks at the properties and characterization of cellulose, chitosan, furanic, starch, wool and silk nanocomposites and the potential industrial applications of natural polymer nanocomposites.With contributions from leading researchers in natural polymers from around the globe, Natural Polymers provides a valuable reference for material scientists, polymer chemists and polymer engineers.
Keywords: Biopolymers.; Nanocomposites (Materials); elektronické knihy; electronic books